Profile of Mathematics Problem Solving for Fourth Grader on Fractional Material Viewed from the Type of Learning Style - Yeni Yusella (Universitas Negeri Malang, 2023)
Abstract: Problem solving is one of the five standard processes that must be developed in mathematics learning. Learning mathematics must prioritize students' ability to solve problems. Problem-solving skills are an important component of learning maths. In order to provide appropriate learning treatment, teachers must know the abilities of students, especially in solving mathematical problems. In this study, an analysis of the stages carried out by students in solving problem solving test questions based on Polya solving steps. But before that, students will be grouped based on their learning style. This research is a qualitative descriptive research. The subjects of this study were 28 grade 4 students of SDN Dinoyo 3 Malang City.After being given a learning style determination questionnaire, 5% of students with visual learning styles, 7% of students with auditorial learning styles, and 28% of students with kinesthetic learning styles were obtained. While 60% of students have the same dominant score on visual-auditorial learning styles. Based on the results of the study, it can be concluded that students show different steps and habits in problem solving. Students with a visual learning style in understanding problems read the questions repeatedly using aloud and fluently and write down important parts of the problem. Students with an auditorial learning style in understanding problems write down parts that they consider important from the problem using mathematical symbols. Students with a kinesthetic learning style in understanding problems write down parts that they consider important from the problem not using their own language. Abstrak: Pemecahan masalah merupakan salah satu dari lima standar proses yang harus dikembangkan dalam pembelajaran matematika. Pembelajaran matematika harus mengutamakan kemampuan siswa dalam pemecahan masalah. Keterampilan pemecahan masalah merupakan komponen yang penting dalam pembelajaran matematika. Agar dapat memberikan treatment pembelajaran yang tepat, guru harus mengetahui kemampuan siswa, khususnya dalam penyelesaian masalah matematika. Dalam penelitian ini dilakukan analisis terhadap tahapan-tahapan yang dilakukan siswa dalam menyelesaikan soal tes pemecahan masalah berdasarkan langkah penyelesaian Polya. Namun sebelumnya siswa akan dikelompokkan berdasarkan gaya belajarnya. Penelitian ini merupakan penelitian deskriptif kualitatif. Subjek penelitian ini adalah 28 siswa kelas 4 SDN Dinoyo 3 Kota Malang.Setelah diberi angket penentuan gaya belajar, diperoleh 5% siswa dengan gaya belajar visual, 7% siswa dengan gaya belajar auditorial, dan 28% siswa dengan gaya belajar kinestetik. Sedangkan 60% siswa mempunyai skor dominan yang sama pada gaya belajar visual-auditorial. Berdasarkan hasil penelitian, dapat disimpulkan bahwa siswa menunjukkan langkah-langkah dan kebiasaan yang berbeda dalam pemecahan masalah. Siswa dengan gaya belajar visual dalam memahami masalah membaca soal dengan berulang-ulang menggunakan suara keras dan lancar serta menuliskan bagian-bagian yang penting dari soal. Siswa dengan gaya belajar auditorial dalam memahami masalah menuliskan bagian-bagian yang dianggapnya penting dari soal dengan menggunakan simbol-simbol matematika. Siswa dengan gaya belajar kinestetik dalam memahami masalah menuliskan bagian-bagian yang dianggapnya penting dari soal tidak dengan menggunakan bahasa sendiri.